Hubungan Jenis dan Siklus Kemoterapi dengan Derajat Neuropati pada Pasien Keganasan - Harlinda Haroen; Indriaty Gimon (Medical Scope Journal, 2024)
Abstract: Antineoplastic chemotherapy agents in cancer treatment can cause peripheral neuropathy. Antineoplastic agents associated with chemotherapy-induced peripheral neuropathy include platinum-based drugs (carboplatin, cisplatin and oxaliplatin) and taxane (paclitaxel and docetaxel). This study aimed to evaluate the relationship between the type and cycle of chemotherapy with the level of neuropathy in malignant patients at Prof. Dr. R. D. Kandou Hospital, Manado, in 2022. The results obtained 43 cancer patients aged 18-65 who underwent chemotherapy, especially drugs from the platinum group (81.4%) such as oxaliplatin (62.8%). The majority of cases were colorectal adenocarcinoma (63%). Using the Toronto Score, the majority of subjects experienced mild neuropathy (55.8%), followed by without neuropathy (32.5%) and moderate neuropathy (11.6%). Although there was an indication of a relationship between the type of chemotherapy and the severity of neuropathy, the results were not statistically significant (p=0.069). In conclusion, there is no relationship between the type and cycle of chemotherapy with the level of neuropathy in cancer patients. Keywords: neuropathy; chemotherapy cycles; types of chemotherapy   Abstrak: Agen kemoterapi antineoplastik dalam pengobatan kanker dapat menyebabkan neuropati perifer. Agen antineoplastik terkait neuropati perifer yang diinduksi kemoterapi termasuk obat berbasis platinum (carboplatin, cisplatin dan oxaliplatin) dan taxane (paclitaxel dan docetaxel). Penelitian ini bertujuan untuk mengetahui hubungan jenis dan siklus kemoterapi dengan keparahan neuropati pada pasien keganasan di RSUP Prof. Dr. R. D. Kandou Manado pada tahun 2022. Hasil penelitian mendapatkan 43 pasien kanker berusia 18-65 tahun yang telah menjalani kemoterapi, khususnya obat berbasis platinum (81,4%) seperti oxaliplatin (62,8%). Jenis keganasan yang terbanyak ialah adenokarsinoma kolorektal (63%). Dengan menggunakan Skor Toronto, didapatkan mayoritas subjek mengalami neuropati ringan (55,9%) diikuti tanpa neuropati (32,5%) dan neuropati sedang (11,6%). Meski ada indikasi hubungan antara jenis kemoterapi dengan tingkat neuropati, hasilnya tidak bermakna secara statistik (p=0,069). Simpulan penelitian ini ialah tidak terdapat hubungan antara jenis dan siklus kemoterapi dengan tingkat neuropati pada pasien keganasan. Kata kunci: neuropati; siklus kemoterapi; jenis kemoterapi